Gambaran Proteinuria Pada Ibu Gravida dengan Preeklamsi dan Eklamsi di Rumah Sakit Umum Daerah Kabupaten Indramayu - Helmy Kurnia Dzulfikar; Indriani Silvia; Wildan Arismunndar S (KOLONI, 2026)
Proteinuria is an important laboratory indicator in pregnant women with preeclampsia and eclampsia because it reflects renal involvement caused by hypertensive disorders of pregnancy. Preeclampsia and eclampsia remain major contributors to maternal and perinatal morbidity and mortality; therefore, early detection through urine protein examination is essential to prevent severe complications. This study aimed to describe proteinuria among gravida women with preeclampsia and eclampsia at the Regional General Hospital of Indramayu Regency. This study used a descriptive design with univariate analysis. The study population consisted of 255 pregnant women who underwent antenatal examination at the Regional General Hospital of Indramayu Regency and met the inclusion criteria. A total of 72 respondents were selected using systematic random sampling. The study variable was positive proteinuria among gravida women with preeclampsia and eclampsia. Secondary data were obtained from medical records using a checklist sheet, then analyzed univariately and presented as frequency distributions and percentages. Most respondents had proteinuria positive I, comprising 47 women (65.3%), followed by proteinuria positive III in 15 women (20.8%) and proteinuria positive II in 10 women (13.9%). Gravida women with preeclampsia/severe preeclampsia accounted for 60 cases (83.3%), while eclampsia was found in 4 cases (5.6%). Most respondents were in the third trimester, totaling 71 women (98.6%).Most respondents had proteinuria positive I, comprising 47 women (65.3%), followed by proteinuria positive III in 15 women (20.8%) and proteinuria positive II in 10 women (13.9%). Gravida women with preeclampsia/severe preeclampsia accounted for 60 cases (83.3%), while eclampsia was found in 4 cases (5.6%). Most respondents were in the third trimester, totaling 71 women (98.6%).